Kamu Sektörü İklimle İlgili Açıklamalar Standardı Taslağının Analizi ve IFRS S2 Standardı ile Karşılaştırılması - Özge SELÇUK; Serap S. YANIK; Yıldız AYANOĞLU (Sayıştay Dergisi)
Climate change necessitates the redefinition of public administration responsibilities not only in environmental terms but also in fiscal, managerial, and social dimensions. Public institutions bear a multi-layered responsibility both for the environmental impacts arising from their own operations and for the outcomes of the public policies they are mandated to implement. In this context, sustainability reporting is no longer merely a voluntary initiative; it has become an integral component of an accountable, transparent, and integrated public financial management framework. This study analyzes the SRS ED 1 Exposure Draft on Climate-related Disclosures, issued by the International Public Sector Accounting Standards Board (IPSASB), as the first sustainability reporting standard designed specifically for the public sector. In addition, the study offers a structural and content-based comparison with IFRS S2 Climate-related Disclosures Standard to highlight the distinctive features of the regulatory framework tailored to the public domain. The findings indicate that, unlike the IFRS S2 Standard, SRS ED 1 mandates the disclosure of public policy outcomes, introduces an expanded definition of materiality, and prioritizes integration with public finance systems—thereby addressing needs unique to the public sector. The effective implementation of SRS ED 1 requires a holistic transformation process encompassing strategic planning, budgeting, performance management, and data infrastructure.